Peningkatan keterampilan menulis kalimat berpola spok dengan model pembelajaran example non example pada siswa kelas IV sekolah dasar - Putri, Devi Kurnia; Koeswanti, Henny Dewi (Trihayu: Jurnal Pendidikan Ke-SD-an, 2025)
This classroom action research aimed to improve the writing skills of fourth-grade students at SD Kristen Satya Wacana in constructing SPOK pattern sentences using the Example Non-Example learning model. This research employed a classroom action research (CAR) design with two cycles and was conducted at SD Kristen Satya Wacana, Salatiga City. The subjects of this classroom action research were 23 fourth-grade students of class 4A at SD Kristen Satya Wacana, consisting of 12 boys and 11 girls. Data was collected and analyzed using quantitative data analysis techniques. The success rate of learning achievement increased from 39% in the pre-cycle to 74% in cycle I and further increased to 87% in cycle II. Based on the results, it can be concluded that the Example Non-Example learning model is effective in improving the writing skills of fourth-grade students at SD Kristen Satya Wacana, Salatiga City in constructing SPOK pattern sentences.